Gender and Welfare Regimes Revised - Connecting Danish and Chinese Perspectives - Abrahamson, Peter (Kvinder, Køn & Forskning, 2015)
China and Denmark could hardly be more different cases for comparison: a huge developing one-party state set against a small post-industrial plural state. Despite these significant and categorical differences, however, both states are faced with similar challenges when it comes to changing demographic patterns, with more elderly persons in need of both care and support, coupled with smaller working-age populations to deliver that care and support. Mapping and comparing the combinations of welfare regarding care for the elderly in China and Denmark reveals serious inequalities of class, gender and generation. Both states are in principle fully committed to the wellbeing of all citizens through universal welfare state protection, but in reality both rely very much on market and civil society solutions, which leaves the population strongly differentiated and polarized, not only when it comes to gender and generation, but also with respect to class. The conclusion is that Denmark and China are converging towards a model of welfare combinations set within an overall framework of universalism. The most important lines of conflict revolve around generation, though class and gender also remain influential.